Integer quantum Hall effect and topological phase transitions in silicene - Liu, Y.L.; Luo, G.X.; Xu, N.; Tian, H.Y.; Ren, C.D. (Condensed Matter Physics, 2017)
We numerically investigate the effects of disorder on the quantum Hall effect (QHE) and the quantum phase
transitions in silicene based on a lattice model. It is shown that for a clean sample, silicene exhibits an unconventional QHE near the band center, with plateaus developing at ν = 0, ±2, ±6, . . ., and a conventional QHE
near the band edges. In the presence of disorder, the Hall plateaus can be destroyed through the float-up of
extended levels toward the band center, in which higher plateaus disappear first. However, the center ν = 0
Hall plateau is more sensitive to disorder and disappears at a relatively weak disorder strength. Moreover, the
combination of an electric field and the intrinsic spin-orbit interaction (SOI) can lead to quantum phase transitions from a topological insulator to a band insulator at the charge neutrality point (CNP), accompanied by
additional quantum Hall conductivity plateaus. Проведено числове дослiдження впливу безладу на квантовий Голiв ефект (КГЕ) та квантовi фазовi переходи у сiлiценi на основi ґраткової моделi. Показано, що у випадку чистого зразка, сiлiцен проявляє
нетрадицiйний КГЕ поблизу центру зони, де утворюються плато при ν = 0, ±2, ±6, . . ., i традицiйний КГЕ
поблизу країв зони. При наявностi безладу, плато Гола можуть бути зруйнованi за рахунок спливання розтягнутих рiвнiв в напрямку до центру зони, де першими зникають вищi плато. Однак, центр ν = 0 плато
Гола є бiльш чутливим до безладу i зникає при вiдносно слабiй силi безладу. Крiм того, поєднання електричного поля та властивої спiн-орбiтальної взаємодiї може призвести до квантових фазових переходiв
вiд топологiчного дiелектрика до зонного дiелектрика у точцi нейтральностi заряду, що супроводжується
утворенням додаткових плато квантової провiдностi Гола.